Radiation and chemical reaction effects on unsteady MHD free convection parabolic flow past an infinite isothermal vertical plate with viscous dissipation - Reddy, B. Prabhakar (Zielona Góra: Uniwersytet Zielonogórski)
The numerical investigation of the effects of radiation and chemical reaction on an unsteady MHD free convection flow with a parabolic starting motion of an infinite isothermal vertical porous plate taking into account the viscous dissipation effect has been carried out. The fluid is considered a gray, absorbing emitting radiation but a non-scattering medium. The dimensionless governing equations for this investigation are solved numerically by applying the Ritz finite element method.
Keywords: radiation parameter; chemical reaction parameter; porous medium; MHD; free convection; isothermal vertical plate